Systematic Review of Mobile Learning Models for Enhancing STEM Access in Public Secondary Schools - Ginikachi Prisca Ifenatuora; Olanrewaju Awoyemi; Fadeke Adeola Atobatele (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
This systematic review explores the landscape of mobile learning models designed to enhance access to STEM education in public secondary schools. Drawing upon theoretical frameworks such as constructivism, socio-cultural learning, and cognitive load theory, the study critically analyzes typologies of mobile learning—including content delivery systems, collaborative platforms, and adaptive learning technologies—and assesses their pedagogical relevance and contextual implementation. The review identifies a diverse range of models that demonstrate potential in improving learner engagement, personalization, and inclusion within STEM subjects. Despite these innovations, the study reveals persistent barriers that hinder effective deployment, including technological limitations, infrastructural disparities, policy fragmentation, and insufficient teacher training. Institutional readiness, curriculum integration, and sustainable funding are highlighted as essential enablers for scaling mobile learning solutions in both urban and rural settings. The paper concludes by offering actionable recommendations for educators, policymakers, and school leaders, and outlines critical directions for future research aimed at fostering equitable, scalable, and culturally responsive mobile learning ecosystems in STEM education.